Arduino based SPWM three phase full bridge inverter for variable speed drive application - Muhamad Aiman, Muhamad Azmi (2016)
The growth of sustainable and renewable energy has become viable with the advancement of the power electronic technology. Industry is one of the area that benefit from this expansion. Induction motor is a work horse for the industry. Variable speed drive (VSD) is introduced to achieve an energy saving and better efficiency performance in induction motor control. However, the cost and complexity of the VSD control restraint its potential for practical use. Digital Signal Processor (DSP) and Field Programmable Gate Array (FPGA) is often used for the microcontroller. Arduino, on the other hand, is a relatively low cost microcontroller that has been used in many applications, but not in power electronics. Therefore, this study is conducted to design and implement the variable speed drive control application using the Arduino. The Sinusoidal Pulse Width Modulation (SPWM) technique is constructed with the look-up table of the sine-wave data and Volt Hertz (V/F) ratio for controlling the speed of a three phase induction machine. The observed Total Harmonic Distortion (THD) is selected as a performance indicator. The variation of sine-wave data and switching frequency is conducted with fixed modulation index and reference frequency of 50 Hz. Results from the simulation presents at 36 points of sine-wave data drive the motor with minimum THD of 6.90% at 18 kHz switching frequency. The limitation of software configuration between Arduino and Simulink restrain the hardware implementation. Therefore, the experimental works with the Arduino Integrated Development Environment (IDE) is needed. Furthermore, the memory usage from the Arduino-Simulink and Arduino-IDE is presented. The memory consumption was reduced by half using the Arduino-IDE with 25,264 bytes compared to the Arduino-Simulink implementation that required 56,300 bytes. In addition, the results from the experiment using Arduino-IDE shows at 36 points of sine-wave data presents a minimum THD of 6.07%. In conclusion, both simulation and experiment agree that a minimum THD result is achieved at 36 sine-wave data with 18 kHz switching frequency are suitable for the variable speed drive application.